The Novel Monoacylglycerol Lipase Inhibitor MJN110 Suppresses Neuroinflammation, Normalizes Synaptic Composition and Improves Behavioral Performance in the Repetitive Traumatic Brain Injury Mouse Model - Prabhuanand Selvaraj; Mikiei Tanaka; Jie Wen; Yumin Zhang (Cells, 2021)
Modulation of the endocannabinoid system has emerged as an effective approach for the treatment of many neurodegenerative and neuropsychological diseases. However, the underlying mechanisms are still uncertain. Using a repetitive mild traumatic brain injury (mTBI) mouse model, we found that there was an impairment in locomotor function and working memory within two weeks post-injury, and that treatment with MJN110, a novel inhibitor of the principal 2-arachidononyl glycerol (2-AG) hydrolytic enzyme monoacylglycerol lipase dose-dependently ameliorated those behavioral changes. Spatial learning and memory deficits examined by Morris water maze between three and four weeks post-TBI were also reversed in the drug treated animals. Administration of MJN110 selectively elevated the levels of 2-AG and reduced the production of arachidonic acid (AA) and prostaglandin E2 (PGE2) in the TBI mouse brain. The increased production of proinflammatory cytokines, accumulation of astrocytes and microglia in the TBI mouse ipsilateral cerebral cortex and hippocampus were significantly reduced by MJN110 treatment. Neuronal cell death was also attenuated in the drug treated animals. MJN110 treatment normalized the expression of the NMDA receptor subunits NR2A and NR2B, the AMPA receptor subunits GluR1 and GluR2, and the GABAA receptor subunits α1, β2,3 and γ2, which were all reduced at 1, 2 and 4 weeks post-injury. The reduced inflammatory response and restored glutamate and GABA receptor expression likely contribute to the improved motor function, learning and memory in the MJN110 treated animals. The therapeutic effects of MJN110 were partially mediated by activation of CB1 and CB2 cannabinoid receptors and were eliminated when it was co-administered with DO34, a novel inhibitor of the 2-AG biosynthetic enzymes. Our results suggest that augmentation of the endogenous levels of 2-AG can be therapeutically useful in the treatment of TBI by suppressing neuroinflammation and maintaining the balance between excitatory and inhibitory neurotransmission.